PENGARUH KOMITMEN PROFESIONAL, LOCUS OF CONTROL DAN SOSIALISASI ANTISIPATIF MAHASISWA TERHADAP WHISTLEBLOWING - Faniati Dian Bakar; Nur Hidayati; Moh. Amin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research was conducted to analyze the "effect of professional commitment, locus of control and anticipatory socialization of students on whistleblowing". The sample in this study was all Accounting Students from the Faculty of Economics and Business, Islamic University of Malang. The analytical method used is Multiple Linear Regression with SPSS 22 For Windows software. Based on the results of simultaneous hypothesis testing shows that simultaneously professional commitment, locos of control and anticipatory socialization of students affect the whistleblowing. Partially it shows that professional commitment, locus of control and anticipatory socialization of students have an effect on whistleblowing.Keywords: “Professional commitment, locus of control and anticipatory socialization affect whistleblowing”.